2020
DOI: 10.3389/fphar.2020.00778
|View full text |Cite
|
Sign up to set email alerts
|

Different Doses of Pharmacological Treatments for Mild to Moderate Alzheimer’s Disease: A Bayesian Network Meta-Analysis

Abstract: Background: Pharmacological treatments play a significant role in treating mild to moderate Alzheimer's disease (AD), but the optimal doses of various drugs used for these treatments are unknown. Our study compared the efficacy, acceptability, and safety of different doses of pharmacological treatments for mild to moderate AD.Methods: Randomized controlled trials (RCTs) were identified by searching the PubMed, EMBASE, and Cochrane Library databases (all RCTs published from the date of inception of the database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 64 publications
1
16
0
Order By: Relevance
“…Terpenoids and flavonoids are two main pharmacological components in Ginkgo extracts (Jacobs & Browner, 2000; Juretzek, 1997). EGb761, the only well‐studied Ginkgo extract at present, has shown beneficial effects on the treatment of vascular disease and neurodegenerative disease such as Alzheimer‐type dementia and insufficient blood flow (Arenz et al, 1996; Juretzek, 1997; Luo et al, 2002; Schmid, 1997; Tu et al, 2020; Weinmann et al, 2010; Zhang, Liu, et al, 2020).…”
Section: Historymentioning
confidence: 99%
“…Terpenoids and flavonoids are two main pharmacological components in Ginkgo extracts (Jacobs & Browner, 2000; Juretzek, 1997). EGb761, the only well‐studied Ginkgo extract at present, has shown beneficial effects on the treatment of vascular disease and neurodegenerative disease such as Alzheimer‐type dementia and insufficient blood flow (Arenz et al, 1996; Juretzek, 1997; Luo et al, 2002; Schmid, 1997; Tu et al, 2020; Weinmann et al, 2010; Zhang, Liu, et al, 2020).…”
Section: Historymentioning
confidence: 99%
“…Currently, both pharmacological and non-pharmacological treatments are often applied for AD, other dementias, or cognitive impairment in older people. At present, only a few symptom-targeted pharmacological treatments are available, which provide modest improvements in patients’ livelihoods, and usually with side effects that may include nausea, dizziness, and weight loss [ 36 , 37 , 38 , 39 ]. For this reason, research on non-pharmacological treatments, which can be well implemented in the daily routine of patients, has increased in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…At present, there is no effective drug for Alzheimer’s disease ( Lu et al, 2020 ; Zhang et al, 2020 ). Doctors or researchers in many fields are trying variable treatment methods.…”
Section: Discussionmentioning
confidence: 99%
“…The current clinical treatment of Alzheimer’s disease with medications has unsatisfactory therapeutic effect. Zhang et al (2020) reported a meta-analysis of pharmacological treatments showing that improvement of Mini-mental State Examination (MMSE) score standard mean difference (SMD) ranges from −0.29 to 0.49; Lu et al (2020) also reported another analysis of anti- Aβ agents for mild to moderate Alzheimer’s disease suggesting no effect of anti- Aβ drugs vs. the placebo group (SMD of MMSE score improvement: −0.29, 95% CI −0.76–0.17; SMD of ADAScog score improvement: MD: 0.20, 95% CI: −0.40–0.81). In contrast, Chu et al (2021) reported a promising result.…”
Section: Introductionmentioning
confidence: 99%